N-Acenoacenes: synthesis and solid-state properties [data] - Wiesner, Thomas (Universität, 2022)
Four N-acenoacenes were synthesized and analyzed for their optoelectronic properties and solid-state packings. Two of the regioisomeric acridinoacr...
Gesehen am 13.10.2022
Keywords: Forschungsdaten; Datenbank